Home computer ownership and educational outcomes of adolescents in Greece - Vladana Djinovic; Nicholas Giannakopoulos (Global Labor Organization (GLO), 2022)
In this paper we investigate whether human capital accumulation, during adolescence, depends on home investments in Information and Communication Technologies (ICT) equipment. Using micro-level data, for children aged 17-18 years old, drawn from the Greek part of the European Union Statistics on Income and Living Conditions (EUSILC) for the period 2003-2019 we measure school dropout for individuals residing in households with and without access to home computer. We found that adolescents with access to ICT have better educational outcomes compared to their peers without access to such equipment (almost 5 percentage points lower probability of school dropout). These estimates are robust to different model specifications and data restrictions. Our results support the hypothesis that technology diffusion promotes educational outcomes and provides additional evidence regarding the formation of human capital during adolescence.
Keywords: I24; O33; J24; 330; Education; Technology Diffusion; Human Capital